2018
DOI: 10.1136/jnnp-2018-318839
|View full text |Cite
|
Sign up to set email alerts
|

Genetic profile and onset features of 1005 patients with Charcot-Marie-Tooth disease in Japan

Abstract: Objective To identify the genetic characteristics in a large-scale of patients with Charcot-Marie-Tooth disease (CMT).MethodsFrom May 2012 to August 2016, we collected 1005 cases with suspected CMT throughout Japan, whereas PMP22 duplication/deletion were excluded in advance for demyelinating CMT cases. We performed next-generation sequencing targeting CMT-related gene panels using Illumina MiSeq or Ion Proton, then analysed the gene-specific onset age of the identified cases and geographical differences in te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
60
3
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 27 publications
16
60
3
8
Order By: Relevance
“…[10][11][12][13][14][15][16] Nevertheless, there are limited data on the effect of targeted NGS panels on the genetic diagnosis of CMT in everyday clinical practice. [17][18][19][20] This study describes the effect of targeted NGS panels on the molecular diagnosis of CMT and related disorders in routine clinical practice in 2 specialized clinics in different health systems in the United Kingdom (London) and United States (Iowa).…”
mentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Nevertheless, there are limited data on the effect of targeted NGS panels on the genetic diagnosis of CMT in everyday clinical practice. [17][18][19][20] This study describes the effect of targeted NGS panels on the molecular diagnosis of CMT and related disorders in routine clinical practice in 2 specialized clinics in different health systems in the United Kingdom (London) and United States (Iowa).…”
mentioning
confidence: 99%
“…The PMP22 duplication accounted for 66.7% of the genetically confirmed CMT cases and was responsible for 48.7% of all CMT patients in our cohort. The proportion of PMP22 duplication among CMT patients in Taiwan was higher than that in U.S., U.K., Germany, Spain and Japan (15–42%) . This phenomenon may come from ethnic differences.…”
Section: Discussionmentioning
confidence: 88%
“…The relatively high percentage of NEFL mutations in our CMT cohort (1.9%) with recurrent mutations of p.P8R and p.E396K (two and three pedigrees, respectively) suggested population‐specific founder effects of the NEFL mutations in Chinese population. NEFL mutations were also relatively prevalent in Japan, accounting for 0.9% and 2.3% of total CMT patients in two Japanese cohorts …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…An estimate of CMT prevalence using data collected for 35 years [11] indicated that all CMT patients had not been diagnosed in Korea. Additionally, the observed increase in prevalence may be partly due to recent advances in molecular diagnosis, including next-generation sequencing, a method that has increased the rate of diagnosis among asymptomatic or mildly affected patients without a family history of CMT [15,16].…”
Section: Discussion/conclusionmentioning
confidence: 99%